Protocol for Screening Water Oxidation or Reduction Electrocatalyst Activity in a Three-Electrode Cell for Alkaline Exchange Membrane Electrolysis - Creel, Erin Brahm; Lyu, Xiang; McCool, Geoff; Ouimet, Ryan J.; Serov, Alexey (Frontiers in Energy Research, 2022)
Accurate and reproducible screening of the electrocatalytic activity of novel materials for Oxygen Evolution Reaction (OER) and Hydrogen Evolution Reaction (HER) requires establishing an easily adoptable harmonized testing protocol. Herein, we describe a robust, instrumentation-independent testing technique utilizing a three-electrode cell with a fully immersed working electrode. Compared to rotating disk electrode (RDE) techniques, this protocol produces current densities close to those obtained in real electrolyzers and eliminates the usage of the expensive RDE apparatus.